Antioxidant Enzyme Activities and Some Biochemical Changes in Rainbow Trout Oncorhynchus mykiss (Walbaum 1792) Yolk-Sac Larvae - Zengin, Hatayi; Yilmaz, Okkes; Gokce, Zehra; Demir, Ersin (Central Fisheries Research Inst, 2016)
In this work we studied the biochemical status of antioxidant defences of yolk-sac larvae from the commercial fish, rainbow trout Oncorhynchus mykiss (Walbaum 1792) over a period of 19 days from hatching. The parameters studied were: superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSHpx), glutathione reductase (GR) and glutathione Stransferase (GST). Oxidative damage was measured by the formation of malondialdehyde (MDA). Our results showed that the presence of catalytic activities was observed from hatching day and significant changes in the enzymes were seen in the 12 and 19 days yolk-sac larvae, when the larvae finished their endogenous feeding. Our study indicates that catalase activity sharply increased in the 12 and 19 days post-hatch but superoxide dismutase activity sharply decreased in the same period. Glutathione peroxidase regularly decreased with age throughout the 19-day study period. Glutathione reductase showed a significant increase in the 12 and 19 days yolk-sac larvae. There were no significant changes in glutathione S-transferase activity throughout the yolk-sac stage. When the egg yolk-sac was reabsorbed, the total protein content sharply decreased at day 19. The PUFA contents in the 12 and 19 days yolk-sac larvae were found to be higher than in the other yolk-sac stage.
Gökkuşağı alabalığı Oncorhynchus mykiss (Walbaum 1792)’in keseli larvalarında antioksidan enzim aktiviteleri ve bazı biyokimyasal değişimler
Keywords: Oncorhynchus mykiss; antioxidant enzymes; yolk-sac larvae; lipid peroxidation; Glutathione (GSH)